Tales from outer suburbia - Tan, Shaun, 1974- (Dorking, England : Templar, 2009)
Fifteen illustrated short stories, some humorous and some haunting, set in the Australian suburbs.
The water buffalo -- Eric -- Broken toys -- Distant rain -- Undertow -- Grandpa's story -- No other country -- Stick figures -- The nameless holiday -- The amnesia machine -- Alert but not alarmed -- Wake -- Make your own pet -- Our expedition -- Night of the turtle rescue.
"Originally published in Australia by Allen & Unwin" -- T.p. verso.
For children.
Keywords: Children's stories, Australian; Suburban life -- Australia -- Juvenile fiction; Australia -- Juvenile fiction; Short stories, Australian